Synthesis and Characterization of Near-Infrared Emissive Chiral π-Conjugated Polymers Incorporating Perylenyl Moieties with Visible-Light Absorption - Li, Junfeng; Chen, Ying; Yang, Chenglong; Lai, Wen-Yong (Synlett, 2015)
A novel set of multifunctional optically active π-conjugated polymers incorporating perylenyl moieties, were designed and synthesized. Chirality transfer and amplification from chiral unit to the main-chain backbone in dilute solution was achieved, which was closely related to the stereocenter in the pendant of a π-conjugated polymer. In addition, annealed films of these polymers exhibited near-infrared emission by direct absorption of visible light, resulting from the introduction of a strong fluorophore perylenyl moiety. Such a design strategy opens up new perspectives for the future development of novel optically active materials with near-infrared emission for photonic applications.
Keywords: π-conjugated polymers; near-infrared emission; visible-light absorption; perylenyl moieties; circular dichroism